Age Bias in Zebrafish Models of Epilepsy: What Can We Learn From Old Fish? - Cho, Sung-Joon; Park, Eugene; Baker, Andrew; Reid, Aylin Y. (Frontiers in Cell and Developmental Biology, 2020)
Zebrafish are a powerful tool for investigating epilepsy. Mammalian seizures can be recapitulated molecularly, behaviorally, and electrophysiologically, using a fraction of the resources required for experiments in mammals. Larval zebrafish offer exceptionally economical and high-throughput approaches and are amenable to state-of-the-art genetic engineering techniques, providing valuable transgenic models of human diseases. For these reasons, larvae tend to be chosen for studying epilepsy, but the value of adult zebrafish may be underappreciated. Zebrafish exhibit transient larval-adult duality. The incompletely developed neural system of larval zebrafish may limit the translation of complex neurological disorders. Larval zebrafish go through dynamic changes during ontogenesis, whereas adult zebrafish are physiologically more stable. Adult zebrafish have a full range of complex brain structures and functions, such as an endothelial blood-brain barrier and adult neurogenesis, both are significant factors in epilepsy research. This review highlights the differences between larval and adult zebrafish that should be considered in pathophysiological and pharmacological studies of epilepsy.